FATHERING IN PARENTING FOR EARLY CHILDREN IN BANYUWANGI CITY EAST JAVA INDONESIA - Noviandari, Harwanti; Agus Mursidi (International Jurnal of Education Schoolars, 2020)
Fathers have an important role in shaping the character of children. The main task of the father as a breadwinner keeps the father busy outside the home, this is the main reason for neglecting the affairs of children's education and care is left entirely to the mother. Children lose quality time with dad. The involvement of fathers in childcare is important for the development of children, the experience experienced by children with fathers will affect children when they are adults. Father and mother togetherness in carrying out the role of care is needed in the development of children, especially the formation of the character of children from an early age. This study uses a qualitative method with a phenomenological approach, for data collection done using observation and interview techniques with the subject of 25 fathers who have children aged 4-7 years, the determination of subjects with purposive sampling. The results of this study illustrate the parenting process that involves the role of fathers (fathering). Fathers have a full awareness of the continuing education and morals and character building of their children, but because of the demands of their living needs to make a living, fathers cannot be fully involved in childcare. Based on the results of the study it is expected that a father is able to be directly involved in the formation of the child's character so that he does not only make a living in the family.